The Crucial Role of Teachers in Fostering Creativity, Critical Thinking, and Motivation in Students - Mastul , Al-Rashiff Hamjilani (The Indonesian Institute of Science and Technology Research, 2024)
This study underscores the critical significance of fostering positive relationships between students and teachers within educational settings. Through an examination of existing literature and research findings, the study illuminates the profound impact of these relationships on various aspects of students' academic performance, social development, and overall well-being. The findings reveal that positive relationships cultivate a collaborative and supportive learning environment wherein students feel empowered to actively engage in the learning process, exchange ideas, and build connections with their peers. Furthermore, the study highlights the role of positive relationships in enhancing students' motivation, resilience, and sense of belonging within the school community. As such, educators are encouraged to prioritize the cultivation of these relationships as a fundamental aspect of effective teaching and student support strategies. This study contributes to a deeper understanding of the critical role that positive relationships play in promoting student success and holistic development in educational contexts.